1999
DOI: 10.1038/sj.bjc.6690809
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of laminin and fibronectin isoforms in oral mucosa and oral squamous cell carcinoma

Abstract: SummaryThe expression of laminin and fibronectin isoforms varies with cellular maturation and differentiation and these differences may well influence cellular processes such as adhesion and motility. The basement membrane (BM) of fetal oral squamous epithelium contains the laminin chains, α2, α3, α5, β1, β2, β3, γ1 and γ2. The BM of adult normal oral squamous epithelium comprises the laminin chains, α3, α5, β1, β3, γ1 and γ2. A re-expression of the laminin α2 and β2 chains could be shown in adult hyperprolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 59 publications
7
107
0
9
Order By: Relevance
“…This is supported by other studies in different tumour types (Zardi et al, 1987;Carnemolla et al, 1989;Castellani et al, 1994;Kaczmarek et al, 1994;Neri et al, 1997;D'Ovidio et al, 1998;Kosmehl et al, 1999;Tarli et al, 1999;Viti et al, 1999;Ebbinghaus et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is supported by other studies in different tumour types (Zardi et al, 1987;Carnemolla et al, 1989;Castellani et al, 1994;Kaczmarek et al, 1994;Neri et al, 1997;D'Ovidio et al, 1998;Kosmehl et al, 1999;Tarli et al, 1999;Viti et al, 1999;Ebbinghaus et al, 2004).…”
Section: Discussionsupporting
confidence: 74%
“…However, it is overexpressed during active tissue remodelling, for example, angiogenesis in tumours, wound healing and embryogenesis Kaspar et al, 2006). It has been shown to accumulate specifically around neovasculature in studies of many different tumour types, making it a good marker for angiogenesis (Carnemolla et al, 1989;Kaczmarek et al, 1994;Neri et al, 1997;Kosmehl et al, 1999;Tarli et al, 1999;Viti et al, 1999;Demartis et al, 2001;Castellani et al, 2002;Birchler et al, 2003;Ebbinghaus et al, 2004).…”
mentioning
confidence: 99%
“…A more recent study demonstrated that oncofetal fibronectins are present throughout the stromal compartment associated with SCC. Further examination revealed that stromal fibro/myofibroblasts were the preferential source of this fibronectin (Kosmel et al, 1999). Thus, in this study it was concluded that in SCC, conversion to a fetal ECM is occurring.…”
Section: Fibronectinmentioning
confidence: 83%
“…11 Thus, all fibroblasts isolated from MM spleen, unlike BM-derived fibroblasts, expressed ␣-sm-actin, ED-B fibronectin and tenascin, which is characteristic of myofibroblasts, found only in pathologic stroma. 17,18 Furthermore, MM spleen-derived fibroblasts also showed higher expression levels of specific surface adhesion molecules for blood cell interactions, i.e., ICAM-1, VLA-4 and CD4 as well as hematopoietic cytokines, i.e., GM-CSF and IL-11.…”
Section: Discussionmentioning
confidence: 99%